Ageing effects on ordering degree and morphology of 18R-type martensite in shape memory CuZnAl alloys - Kayali, N; Ozgen, S; Adiguzel, O (Pergamon-Elsevier Science Ltd, 1997)
Ageing effects in CuZnAl alloys have been investigated by X-ray diffraction and optical microscopy. The splittings observed in some selected diffraction peaks due to the monoclinicity of the martensite unit cell by basal plane distortion are referred to as monoclinic distortion. The spacing difference, Delta d, between some selected pairs of peaks may be used as a parameter to reflect the ordering degree in CuZnAl alloys, and the extent of Delta d difference and monoclinic distortion may depend on the type and degree of long range order or alloy composition. The variation of Delta d parameters for both as-quenched and post-quench beta-phase annealed specimens show a trend to decrease with holding duration at room temperature. This trend is closely related to the martensite stabilization, and this process is mainly due to the rearrangement of atoms in martensite lattice. Self-accommodating martensite morphology which has a diamond-like configuration has been observed in both as-quenched and post-quench heat-treated specimens. Parallel bands defined as lamellar martensite or twin-like morphologies have also been formed on the martensite plates, and interlamellar boundaries are not as straight as twin boundaries. Copyright (C) 1997 Elsevier Science Ltd.
Keywords: alloys; X-ray diffraction; crystal structure; phase transitions